Institutional variation in recovery after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: An opportunity for enhanced recovery pathways. Issue 5 (5th July 2020) - Eng, Oliver S.; Blakely, Andrew M.; Lafaro, Kelly J.; Fournier, Keith F.; Fackche, Nadege T.; Johnston, Fabian M.; Dineen, Sean; Powers, Benjamin; Hendrix, Ryan; Lambert, Laura A.; Ronnekleiv‐Kelly, Sean; Walle, Kara Vande; et al.
Abstract: Background: Variations in care have been demonstrated both within and among institutions in many clinical settings. By standardizing perioperative practices, Enhanced Recovery After Surgery (ERAS) pathways reduce variation in perioperative care. We sought to characterize the variation in cytoreductive surgery (CRS)/heated intraperitoneal chemotherapy (HIPEC) perioperative practices among experienced US medical centers. Methods: Data from the US HIPEC Collaborative represents a retrospective multi‐institutional cohort study of CRS and CRS/HIPEC procedures performed from 12 major academic institutions. Patient characteristics and perioperative practices were reported and compared. Institutional variation was analyzed using hierarchical mixed‐effects linear (continuous outcomes) or logistic (binary outcomes) regression models. Results: A total of 2372 operations were included. CRS/HIPEC was performed most commonly for appendiceal histologies (64.2%). The rate of complications (overall 56.3%, range: 31.8‐70.9) and readmissions (overall 20.6%, range: 8.9‐33.3) varied by institution ( P < .001). Institution‐level variation in perioperative practice patterns existed among measured ERAS pathway process/outcomes ( P < .001). The percentages of variation with each process/outcome measure attributable solely to institutional practices ranged from 0.6% to 66.6%. Conclusions: Significant variation exists in the perioperative care of patients undergoing CRS/HIPEC at major US academic institutions. These findings provide a strong rationale for the investigation of best practices in CRS/HIPEC patients.